The Sovereign Wealth Funds of European Union Member States - Kulbacki, Michał (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: The article has two objectives: to evaluate the activities of the sovereign wealth funds of EU member states, and to identify the strengths and weaknesses in their functioning.Research Design & Methods: The study uses the original Indicator of Assessment of Sovereign Wealth Funds (the SWF Indicator), an analysis of information and data on these funds, and comparative analysis.Findings: The activity of the sovereign wealth funds was assessed as moderately positive. Their strengths include their institutional foundations, governance and portfolio management. The weaknesses include a failure to  achieve environmental, social and ethical goals, as well as the support of economic policy.Implications / Recommendations: The implications presented in the paper show that sovereign wealth funds should take measures to address their weaknesses. For this purpose, they can rely on good practices identified in the study.Contribution: A comprehensive assessment of the activities of EU Member States’ sovereign wealth funds.